Strategies to Promote Student's Autonomous Reading Motivation - Haninah Haninah; Alies Poetri Lintangsari (Universitas Brawijaya, 2018)
Reading English text is challenging for senior high school students, therefore the teacher has to provide effective strategies to motivate the students to read more. This study aims to identify the teacher’s strategies called Independent Study to promote student's autonomous reading motivation. It is a case study using triangulation data involving the English teacher and 27 students of the 12th Grade of SMKN 1 Batu majoring in Hospitality Management. The data were collected from interviews, observations, and questionnaires based on Self-Determination Theory (SDT) and were analyzed both quantitatively and qualitatively. The results pointed out that the teacher applied all of the strategies of SDT teaching dimensions (autonomy support, structure, and involvement) which were effective to encourage students reading motivation. It is proven by the results of two questionnaires: (1) Teacher as Social Context Questionnaire (TASC) indicating that students' perceptions on teaching dimensions were good and (2) Self-Regulation Questionnaire (SRQ) indicating that the students had both extrinsic (external and identified regulation) and intrinsic reading motivation.